(untitled) (Sinología hispánica. China Studies Review, 2018)
Based on the theory of Flow experience, this thesis combines the theory of perceived value with the theory of customer innovation, and constructs the influencing factor model of Smartphone users’ purchase intention. The paper aims to understand the impact of Flow experience in the intention of mobile shopping in China. To address this, an empirical study with 430 subjects was carried out. It collected the data by questionnaire with 5-point Likert scale, and used SPSS.22.0 and AMOS.21 to encode and analysis the data by the method of factor analysis, descriptive statistics and structural equation modeling. The results indicate that flow experience has a significant positive effect on the purchase intention of mobile shopping, and customer innovation has a direct effect on flow experience which in turn impacts purchase intention. Furthermore, this study also reveals that perceived value influence mobile shopping deeply. Key words: Mobile shopping